Accounting information quality and tax avoidance effect on investment opportunities evidence from Gulf Cooperation Council GCC - Ahnaf Ali Alsmady (Cogent Business & Management, 2022)
The motivation of this research is to investigate the important factors that affect Gulf Cooperation Council (GCC) economies and increase the investment opportunities to avoid the threats of limited oil resources in the future. This study examines the relationship between tax avoidance, accounting information quality, and other control variables on investment opportunities in six Arabian GCC countries, namely Bahrain, Oman, Qatar, Saudi Arabia, Kuwait, and the United Arab Emirates (UAE). Moreover, this research investigates whether the accounting information quality affects the tax avoidance investment opportunities relationship. The data sample of the study includes 191 companies over the period of 2011 to 2017 (1337 company-year observations). This study used ordinary least squares (OLS) and moderated multiple regression (MMR) models for direct and moderation effects of accounting information quality, respectively. This study demonstrates that tax avoidance has a significant negative effect on investment opportunities, while the accounting information quality has a significant positive effect on investment opportunities. In line with the agency theory perspective, the high accounting information quality mechanism leads to the control of the managers' opportunist behaviour, mitigates information asymmetry in managers and increases investment opportunities. Moreover, further analysis found that accounting information quality positively moderates the relationship between the tax avoidance and investment opportunities. Thus, higher quality of accounting information is strongly recommended to companies and policymakers, where tax planning is used as an alternative source of cash to achieve higher investment opportunities in GCC countries.
Keywords: 650; accounting information quality; Gulf Cooperation Council (GCC); investment opportunities; Tax avoidance